KOSAKONIA SP. PROTEOLYTIC BACTERIA ISOLATED FROM RUMEN AND RETICULUM OF ACEH CATTLE - Safika, Safika; Sari, Wenny Novita; Ademi, Gressha Vionalle; Arsih, Ulfi Widi; Darmawi, Darmawi (Universitas Syiah Kuala, 2020)
The aim of this study was to identify proteolytic bacteria from the ruminal and reticulum fluids of aceh cattle based on the 16S rRNA gene. Samples used were ruminal and reticulum fluids of aceh cattle slaughtered in Abattoir of Aceh Besar. Samples were diluted and cultured into Skim Milk Agar medium at 39 C for 48 hours. The morphology of bacterial colonies growth in the medium was observed. Colonies resulted in the largest clear zone were isolated and used for Deoxyribonucleic Acid (DNA) isolation, 16S rRNA gene amplification and sequencing. Theresults showed that morphology of dominant colonies was yellowish white color, round shape, position on the agar surface. The results ofphylogenetic analysis of RS1 and ReS2 isolates isolated from rumen and reticulum fluids of aceh cattle respectively had a close familialrelationship and belonged to the bacterial group of Kosakonia. Sequence homology showed isolate RS1 and ReS2 are probably either newEnterobacteriaceae species or unconfirmed species. Halo zone produced by ruminal bacteria had a wider diameter (25 mm vs 20 mm) than thatcaused by reticulum bacteria). Based on the results, RS1 (bacterium in the rumen) and ReS2 (bacterium in the reticulum) belong to similar type, namely Kosakonia sp. with a proteolytic activity. Presumably, these bacteria originate from the rumen that enters the reticulum with degraded feed.